Analysis of Price, Quality of Service and Location on Purchase Decisions at 3 Putra Flower Shop Baron, Nganjuk - Nofian, Bayu; Muslih, Basthoumi; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2023)
Research Objective:The purpose of this study was to analyze the effect of price, service quality, and location on purchasing decisions at 3 Putra Baron Flower Shop, Nganjuk either partially or simultaneously. Research Method: The approach used in this study is a quantitative approach and the type of causal research, the sampling technique uses multivariete analysis, the sample size used is 40 respondents, and the data analysis technique uses descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and test hypothesis with SPSSv25 tool. Research Finding: The results showed that price and location had a significant effect, service quality did not have a significant effect, and there was a significant effect between price, service quality, and location simultaneously on purchasing decisions.